STRATEGI MENDIDIK GENERASI Z DI ERA DIGITAL PERSPEKTIF TEORI SOSIOLOGI - M. Fauzan; Marta Novika; Muhiddinur Kamal; Hendrisab (STKIP Subang, 2025)
The concept of theory is often understood in various ways, ranging from views that consider it unrealistic to those that see it as impractical. As an effort to interpret social phenomena, theory plays a crucial role in answering the question of